Blunt trauma of unilateral intraperitoneal kidney: A case report. (August 2018) - Chang, Ye Rim; Yun, Jeongseok; Kim, Dong Hun
Abstract: The kidney is located and fixed with Gerota's fascia in the retroperitoneal space and is surrounded by a fat pad that acts as a shock absorber in the normal anatomy; however, the kidney becomes more vulnerable to external shock when it is located intraperitoneally. Bleeding from an injury may advance to hemoperitoneum and unstable hemodynamics may develop, requiring emergency surgery. Although various anatomical variations of the kidney have been reported, to our knowledge, an intraperitoneal kidney has never been reported previously except for one case in the world literature. This paper describes a successful nephrectomy of a unilateral intraperitoneal kidney in a 69-year-old woman who had grade IV laceration based on the renal injury scale of the American Association for the Surgery of Trauma with unstable hemodynamics after blunt trauma.